The level of aerobic and anaerobic capacity and the results of a special mobility fitness test of female judo competitors aged 16-18 years - Wolska-Paczoska, B. (Baltic Journal of Health and Physical Activity, 2010)
Background: The purpose of this work is to determine the correlation between the indexes of the special fitness test and the parameters of aerobic and anaerobic capacities of women judo competitors, during the preparation period to competitions.